A Proposed Syllabus for EFL Writing Class at University - Hanna Sundari; Rina Husnaini Febriyanti; Gustaman Saragih (Lingua Cultura, 2018)
This present study intended to develop the first draft syllabus for writing course in English Education major. Particularly in teaching writing as foreign language, syllabus became one of the key factors for teachers before and while delivering thelesson. The research was carried out by initial steps of research and development approach (R and D). The respondents were the students from writing classes, writing lecturers, and the stakeholders in one university in Jakarta. In collecting data, the instruments were the questionnaire and in-depth interview. After analyzing the data from need analysis descriptively, the researchers have modeled a developed layout of the syllabus for writing class. The syllabus is developed in a set of concepts and rationale, general and specific objectives or outcomes of the course as competences, teaching methods, materials and content, practices and activity, and evaluation.